2015
DOI: 10.1093/pubmed/fdv096
|View full text |Cite
|
Sign up to set email alerts
|

Nudging healthy food choices: a field experiment at the train station

Abstract: Repositioning healthy foods is a simple, effective and well-accepted nudge to increase healthy purchases. Moreover, disclosing its purpose does not impact on effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
157
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 213 publications
(202 citation statements)
references
References 13 publications
14
157
1
4
Order By: Relevance
“…Thereby, it is relevant to note that a majority of employees were positive about the nudge intervention. This aligns with prior research indicating that people are generally appreciative of nudges that help them perform health behaviours (Kroese et al, 2016;Junghans, Cheung, & De Ridder, 2015). Only a minority of 11% indicated to disapprove of the nudge intervention, which is low when placing this percentage in the context of nudge approval in general: a recent paper by Reisch and Sunstein (2016) indicated that 42% of their polled Europeans disapproved of the presented default nudges.…”
Section: Contributionssupporting
confidence: 83%
See 1 more Smart Citation
“…Thereby, it is relevant to note that a majority of employees were positive about the nudge intervention. This aligns with prior research indicating that people are generally appreciative of nudges that help them perform health behaviours (Kroese et al, 2016;Junghans, Cheung, & De Ridder, 2015). Only a minority of 11% indicated to disapprove of the nudge intervention, which is low when placing this percentage in the context of nudge approval in general: a recent paper by Reisch and Sunstein (2016) indicated that 42% of their polled Europeans disapproved of the presented default nudges.…”
Section: Contributionssupporting
confidence: 83%
“…Pichert & Katsikopoulos, 2008; (Ф = .26)), healthy eating (e.g. Kroese, Marchiori, & de Ridder, 2016; (pη 2 = .49)) and saving money (e.g. Choi, Laibson, Madrian, & Metrick, 2004).…”
mentioning
confidence: 99%
“…the healthy choice) easier to make (Thaler & Sunstein, 2008). Examples of healthy eating nudges include placing fruit at the cash registry instead of candy bars, which increased fruit intake (Kroese, Marchiori, & De Ridder, 2016), implicitly signalling a social norm by displaying packaging of healthy snacks, influencing food choice between healthy and unhealthy food choices (Prinsen et al, 2013), traffic light labelling of foods, leading to increased nutrient knowledge as well as identification of health as an important factor in purchasing decisions (Roberto et al, 2012;Sonnenberg et al, 2013), and changing default portion sizes or choices, although results are mixed: one paper reports similar energy intake with smaller versus bigger plates, with bigger plates having the advantage of more vegetable sidedishes (Libotte, Siegrist, & Bucher, 2014) whereas another warns against the danger of overeating with big plates (Wansink & Van Ittersum, 2013).…”
Section: Physical Environmentmentioning
confidence: 99%
“…The latter used a fake food buffet, 13 a Foodscape Laboratory 26 and an online shelf-display. 27 In the field studies, different settings were involved, including dining facilities or cafeterias in schools (11), cafeterias in hospitals (2) as well as restaurants, buffet lines at conferences (2; 28,29 ), a cafeteria at a workplace, 30 a university, 31 a train station, 32 corner stores 33 and a swimming pool. 34 Most studies used a within subjects pre-post interventions design (10), or a between subjects design with a control and treatment group (9), while a minority used both a between-and within subjects design (4).…”
Section: Narrative Synthesismentioning
confidence: 99%